Characterization of convergence in fuzzy topological spaces - E. Lowen; R. Lowen (International Journal of Mathematics and Mathematical Sciences)
In a fuzzy topology on a set X, the limit of a prefilter (i.e. a filter in the lattice [0,1]X) is calculated from the fuzzy closure. In this way convergence is derived from a fuzzy topology. In our paper we start with any rule lim which to any prefilter 𝔇 on X assigns, a function lim𝔇∈[0,1]X. We give necessary and sufficient conditions for the function 𝔇→lim𝔇 in order that it can be derived from a fuzzy topology.